Edukasi dan Pelatihan Penggunaan Kompres Hangat untuk Mengatasi Nyeri Payudara pada Ibu Menyusui di PMB Lismarini - Devina Anggrainy (Lembaga Pengembangan Kinerja Dosen, 2025)
Breast pain is one of the common problems often experienced by breastfeeding mothers, especially in the early stages of lactation. If not treated properly, breast pain can cause discomfort, disruption in breastfeeding, and a decrease in the mother's quality of life. This community service activity aims to provide education about the causes and impacts of breast pain in breastfeeding mothers, train breastfeeding mothers in the effective use of warm compresses to reduce breast pain, improve the quality of life of breastfeeding mothers through proper pain management. The stages of the activity consist of preparation, education, training and evaluation. The results of the activity obtained an increase in the average knowledge score from 60% (pre-test) to 84% (post-test), participants successfully practiced the technique of using warm compresses correctly and several participants reported a decrease in pain after trying the warm compress technique at home for a week. This program has the potential to be further developed by involving a wider community.